Young-Onset Colon Cancer and Recurrence Risk by Gene Expression. (5th February 2020) - Chang, George J; You, Y Nancy Y; Russell, Christy A; Tierno, Marni B; Turner, Michelle; Bennett, John P; Lau, Anna; Hochster, Howard S
Abstract: The incidence and mortality from colorectal cancer in younger adults (younger than 55 years) is increasing. We reviewed the complete database of a gene-expression test, Oncotype DX Colon Recurrence Score test, to determine age-related differences in recurrence score (RS) and single-gene results (7 cancer-related of the 12-gene assay). We included 20 478 stage II and III A and B colon cancer patients submitted to Genomic Health. RS results were grouped by low-, intermediate-, and high-risk groups. Single-gene scores were described using median and interquartile range. Of all patients 72.5% and 72.6% of those younger than 40 years had low-risk RS. Comparing older with younger patients, RS or single-gene expression did not differ by age group or stage. Young-onset colon cancer does not differ by expression of the RS component genes. Most patients with stage II and III colon cancer have low-risk disease as measured by the 12-gene assay, regardless of age.